Secondhand smoke exposure and risk of lung cancer in Japan: a systematic review and meta-analysis of epidemiologic studies - Hori, Megumi; Tanaka, Hirokazu; Wakai, Kenji; Sasazuki, Shizuka; Katanoda, Kota (Japanese journal of clinical oncology, 2016)
Systematic evaluation of the association between secondhand smoke exposure and lung cancer in Japan has yet to be conducted. Here, we performed a systematic review and meta-analysis of the relationship between secondhand smoke and lung cancer in Japanese non-smokers. Relevant studies were collected from the MEDLINE and Ichushi Web databases using a combination of search terms and Medical Subject Headings. Eligible studies were identified, and relative risks or odds ratios were extracted to calculate pooled risk estimates. This procedure was performed independently by at least two authors. Stratified analyses were carried out according to study design, publication year, and whether or not potential confounding variables were accounted for. The presence of publication bias was assessed via funnel plots. We identified four cohort studies and five case-control studies. Quantitative synthesis was conducted only for secondhand smoke exposure in the home during adulthood. Of the 12 populations included in meta-analysis, positive secondhand smoke exposure-lung cancer associations were observed in 11, whereas an inverse association was found in the remaining 1. The pooled relative risk of lung cancer associated with secondhand smoke exposure was 1.28 (95% confidence interval: 1.10-1.48). We found no evidence of publication bias, and a significant association remained even when potentially missing studies were included (pooled relative risk: 1.26; 95% confidence interval: 1.09-1.46). The results were stable across different subgroup analyses, including by study design, publication year, and when adjusting for confounding variables. Secondhand smoke exposure in the home during adulthood results in a statistically significant increase in the risk of lung cancer.